Muted responses to Ag accumulation by plankton to chronic and pulse exposure to silver nanoparticles in a boreal lake - Beth C. Norman; Paul C. Frost; Graham C. Blakelock; Scott N. Higgins; Md Ehsanul Hoque; Jennifer L. Vincent; Katarina Cetinic; Marguerite A. Xenopoulos (Canadian Science Publishing, 2019)
Silver nanoparticles (AgNPs) are an emerging class of contaminants with the potential to impact ecosystem structure and function. AgNPs are antimicrobial, suggesting that microbe-driven ecosystem functions may be particularly vulnerable to AgNP exposure. Predicting the environmental impacts of AgNPs requires in situ investigation of environmentally relevant dosing regimens over time scales that allow for ecosystem-level responses. We used 3000 L enclosures installed in a boreal lake to expose plankton communities to chronic and pulse AgNP dosing regimens with concentrations mimicking those recorded in natural waters. We compared temporal patterns of plankton responses, Ag accumulation, and ecosystem metabolism (i.e., daily ecosystem respiration, gross primary production, and net ecosystem production) for 6 weeks of chronic dosing and 3 weeks following a pulsed dose. Ag accumulated in microplankton and zooplankton, but carbon-specific Ag was nonlinear over time and generally did not predict plankton response. Ecosystem metabolism did not respond to either AgNP exposure type. This lack of response corresponded with weak microplankton responses in the chronic treatments but did not reflect the stronger microplankton response in the pulse treatment. Our results suggest that lake ecosystem metabolism is somewhat resistant to environmentally relevant concentrations of AgNPs and that organismal responses do not necessarily predict ecosystem-level responses.